The Unified Patent Court and Non-Practicing Entities in Europe - Quelhas, José Maria Lopes Pires Santos (2019)
Under the European Patent Convention, applicants can seek patent protection in several jurisdictions in one single application before the European Patent Office. However, the post-grant life of the patent implies the application of as many patent laws as the jurisdictions which the applicant designates. Thus, the right holder has a bundle of national patents, which implies the risk of parallel patent litigation and its often prohibitive costs. The Unitary Patent Package proposes to create a European Patent with Unitary Effect as a single object of property, recognized throughout the European Union, to which one law only is applicable. It also aims to create a centralized Court for the enforcement of European and European Patents with Unitary Effect. Our main research question will be that of understanding the possible relationship between the Unified Patent Court and Non-Practicing Entities activity in Europe. In order to gain a proper understanding of the problem, we will firstly consider the current issues with the transnational enforcement of patent rights, namely, income distribution inequalities. Secondly, we will address the Unitary Patent Package legality under European Union and international law. Thirdly, we will revisit the purpose of patent law and understand its evolution towards patent monetization. Fourthly, we must understand the current patent market characteristics and define a Non-Practicing Entity. Afterwards, we will seek to understand these entities under recent empirical research. Finally, we will place the proposed European Patent with Unitary Effect on the current framework of patent protection in Europe, and finally analyze the provisions which may be favorable to Non-Practicing Entity’s activities.